Nephropathies in the elderly - Stompór, Tomasz (Przewodnik Lekarza/Guide for GPs, 2006)
According to the ”traditional” approach kidney function gradually decreases with age; however, recent epidemiological observations suggest that in many otherwise healthy elderly people kidney function is well preserved. The progressive loss of renal function with ageing seems to be caused by several (apparently not clinically important) damaging factors rather than the ”physiological” kidney ageing. One cannot exclude that the number of nephrons present at birth in certain individual may also be important in determining the vulnerability of the kidneys to damage during the lifespan. The course of kidney diseases in elderly patients frequently differs from that found in other age groups; it is important to realize these differences. The treatment of nephropathies in older people, in principle similar to that in other periods of life, is also characterized by several important differences.